Manganese-enhanced magnetic resonance imaging in the whole visual pathway: chemical identification and neurotoxic changes. (December 2019) - Xiao, Zebin; Tang, Zuohua; Wu, Lingjie; Feng, Xiaoyuan; Sun, Xinghuai; Tang, Weijun; Wang, Jie; Jin, Lixin; Wang, Rong
Background: Little is known about the specificity of manganese-enhanced magnetic resonance imaging (MEMRI) and its neurotoxic effect of the whole visual pathway. Purpose: To explore the specificity of MEMRI and the neurotoxic effect in the whole visual pathway. Material and Methods: Twenty-four rats were divided into four groups, in which 50, 100, 200, and 400 nmol MnCl2 were injected into the left eye of each rat through intravitreal injection, respectively. MEMRI was performed one day after injection of MnCl2 . Moreover, another 10 rats were divided into two groups, in which 200 and 400 nmol MnCl2 were injected into the left eye of each rat. One day after injecting, chemical identification and transmission electron microscopy were performed to verify the presence and pathological effects. Results: The whole three-dimensional (3D) visual pathway of the left eye was observable on MEMRI with thin slab maximum intensity projection (TSMIP) in all rats except the 50 nmol group, which was confirmed by chemical identification. Higher dose of MnCl2 resulted in greater contrast-to-noise ratio, increasing the effectiveness of the technique. Transmission electron microscopy showed most structures of the visual pathway except the superior colliculus and visual cortex were poisoned in the 200 and 400 nmol groups, especially in the latter group. Conclusion: Our study indicated that MEMRI with TSMIP after injection of 200 nmol MnCl2 can best show the entire and 3D visual pathway in the rat with less neurotoxic changes. Additionally, chemical identification is useful for the confirmation of the specificity of MEMRI.